The trader's guide to key economic indicators - Yamarone, Richard (Bloomberg Press, 2007)
"This book presents the twelve most important economic indicators, plus several others from fixed-income and commodity markets that have been added in this revised and expanded edition. These key indicators are among the most valuable of any analyst's or economist's tools for understanding and predicting what will happen in the markets"--Provided by publisher.